2012
DOI: 10.1111/j.1600-0897.2012.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity Study of Plasmid DNA Encoding Mouse Cysteine‐Rich Secretory Protein‐1 (mCRISP1) as a Contraceptive Vaccine

Abstract: Problem To examine the immunocontraceptive properties of the plasmid pcDNA‐mCRISP1 and compare them to the corresponding recombinant mCRISP1 (r‐mCRISP1). Method of study RT‐PCR and indirect immunofluorescence were performed to observe the mCRISP1 protein expression in COS‐7 cells. Three groups of mice received three injections of r‐mCRISP1, pcDNA‐mCRISP1 or pcDNA vector, respectively. ELISA and Western blot were used to examine the immune responses and immunoreactivity of antisera. Sperm‐egg penetration assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…This strategy is based on the induction of antibodies against epididymal or testicular proteins so that they do not associate with the sperm surface or mask them to prevent interaction with other proteins for maturation. Examples include: antisperm antibodies (Vazquez-Levin (Luo et al, 2012), eppin (O'Rand et al, 2006), Bin1b (Li et al, 2001), FA-1 (Naz and Zhu, 1998), LDH-C4 (O'Hern et al, 1997), P10G (O'Rand et al, 1993, A9D (Lea et al, 1998), SP56 (Hardy and Mobbs, 1999), 80 kDa HSA (Khobarekar et al, 2008), YLP12 (Naz and Chauhan, 2002), zona pellucida proteins (Eade et al, 2009), and Izumo (Naz, 2008;Wang et al, 2009). We previously demonstrated that the rat PATE proteins are localized on the sperm surface and are predicted to play a role in sperm function (Rajesh and Yenugu, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy is based on the induction of antibodies against epididymal or testicular proteins so that they do not associate with the sperm surface or mask them to prevent interaction with other proteins for maturation. Examples include: antisperm antibodies (Vazquez-Levin (Luo et al, 2012), eppin (O'Rand et al, 2006), Bin1b (Li et al, 2001), FA-1 (Naz and Zhu, 1998), LDH-C4 (O'Hern et al, 1997), P10G (O'Rand et al, 1993, A9D (Lea et al, 1998), SP56 (Hardy and Mobbs, 1999), 80 kDa HSA (Khobarekar et al, 2008), YLP12 (Naz and Chauhan, 2002), zona pellucida proteins (Eade et al, 2009), and Izumo (Naz, 2008;Wang et al, 2009). We previously demonstrated that the rat PATE proteins are localized on the sperm surface and are predicted to play a role in sperm function (Rajesh and Yenugu, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm maturation is facilitated by a number of proteins secreted by the epididymal epithelial cells into the luminal fluid, which then bind on to the sperm surface (Ducheux et al, 2003). Defensins (Yenugu et al, 2004(Yenugu et al, , 2006Travis et al, 2000), members of the sperm-associated antigen 11 family (Hamil et al, 2000), lysozymes Mandal et al, 2003), lipocalins (Hamil et al, 2003), cathelicidins, protease inhibitors Blankenvoorde et al, 1998;Hiemstra et al, 1996), inhibitors of complement lysis (Collard and Griswold, 1987;Griswold et al, 1986), the cysteine-rich proteins such as CRISPs (Jalkanen et al, 2005;Luo et al, 2012), and members of the prostate-and testis-expressed (PATE) family (Bera et al, 2002;Soler-Garcia et al, 2005;Levitin et al, 2008;Turunen et al, 2011) are some examples of a wide range of proteins that bind to the sperm surface . Further, a variety of factors secreted by the seminal vesicles and prostate also aid in the formation of functional http://dx.doi.org/10.1016/j.jri.2015.02.009 0165-0378/© 2015 Elsevier Ireland Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 97%
“…Development of contraceptive vaccines for males is of great importance for global population control. Up to the present, many efforts have been put into developing male contraceptive vaccines 4725. Although the hormonal approach to male contraception has made significant progress in the last decade, it has encountered bottlenecks because of the non-ignorable side effects 262728.…”
Section: Discussionmentioning
confidence: 99%
“…Data from animal experiments and some clinical trials provide several good male contraception targets 5678. Among these, follicle-stimulating hormone (FSH) has been paid more attention for its importance in quantitatively and qualitatively normal spermatogenesis and spermatogonial maturation 910.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, our group constructed a genetic immunocontraceptive vaccine‐based mouse CRISP1 (mCRISP1), which then be demonstrated can successfully elicit anti‐mCRISP1 antibodies in both male and female BALB/c mice and the antibodies thus generated recognized native CRISP1 protein in mouse sperm . However, the antifertility effect of the mCRISP1 DNA vaccine on mice is not satisfactory.…”
Section: Introductionmentioning
confidence: 99%